Cosmogenic Be-10 exposure dating of glacial erratics on Horseshoe Island in western Antarctic Peninsula confirms rapid deglaciation in the Early Holocene - Ciner, Attila; Yildirim, Cengiz; Sarikaya, M. Akif; Seong, Yeong Bae; Yu, Byung Yong (CAMBRIDGE UNIV PRESS, 2019)
The rapid warming observed in the western Antarctic Peninsula gives rise to a fast disintegration of ice shelves and thinning and retreat of marine-terminating continental glaciers, which is likely to raise global sea levels in the near future. In order to understand the contemporary changes in context and to provide constraints for hindcasting models, it is important to understand the Late Quaternary history of the region. Here, we build on previous work on the deglacial history of the western Antarctic Peninsula and we present four new cosmogenic Be-10 exposure ages from Horseshoe Island in Marguerite Bay, which has been suggested as a former location of very fast ice stream retreat. Four samples collected from erratic pink granite boulders at an altitude of similar to 80 m above sea level yielded ages that range between 12.9 +/- 1.1 ka and 9.4 +/- 0.8 ka. As in other studies on Antarctic erratics, we have chosen to report the youngest erratic age (9.4 +/- 0.8 ka) as the true age of deglaciation, which confirms a rapid thinning of the Marguerite Trough Ice Stream at the onset of Holocene. This result is consistent with other cosmogenic age data and other proxies (marine and lacustrine C-14 and optically stimulated luminescence) reported from nearby areas.
Keywords: SOUTH SHETLAND ISLANDS; VI ICE SHELF; MARGUERITE BAY; HISTORY; RETREAT; MAXIMUM; STREAM; CONSTRAINTS; FJORD; RATES